Total Humeral Endoprosthetic Replacement following Excision of Malignant Bone Tumors. (21st February 2016) - Kotwal, Suhel; Moon, Bryan; Lin, Patrick; Satcher, Robert; Lewis, Valerae
Abstract : Humerus is a common site for malignant tumors. Advances in adjuvant therapies and reconstructive methods provide salvage of the upper limb with improved outcomes. Reports of limb salvage with total humeral replacement in extensive humeral tumors are sparse. We undertook a retrospective study of 20 patients who underwent total humeral endoprosthetic replacement as limb salvage following excision of extensile malignant tumor from 1990 to 2011. With an average followup of 42.9, functional and oncological outcomes were analyzed. Ten patients were still alive at the time of review. Mean estimated blood loss was 1131 mL and duration of surgery was 314 minutes. Deep infection was encountered in one patient requiring debridement while mechanical loosening of ulnar component was identified in one patient. Subluxation of prosthetic humeral head was noted in 3 patients. Mean active shoulder abduction was 12.5° and active flexion was 15°. Incompetence of abduction mechanism was the major determinant of poor active functional outcome. Mean elbow flexion was 103.5° with 30.5° flexion contracture in 10 patients with good and useful hand function. Average MSTS score was 71.5%. Total humeral replacement is a reliable treatment option in restoring mechanical stability and reasonable functional results without compromising patient survival, with low complication rate.